Vouloir construire une mosquée en pays Jola - Ajamat (Guinée Bissau, 1990 – 2000) - André Julliard (Revue des Mondes Musulmans et de la Méditerranée)
Three religions cohabitate – not without occasional conflicts – in Susana, the largest rice-producing town in Diola Adiamat country, in the northwest of Guinea-Bissau. The “religion of the soil” (the idea that a unique God coexists alongside superhuman polytheistic activity) remains prevalent in a demographic sense. Catholicism has a high conversion rate and Islam progresses thanks to merchant establishments and the influx of refugees from the Casamance military conflict in neighbouring Senegal. Sacrificial areas, usually without fences, stitch the landscape of villages and farms. To the south, Susana is bordered by the concrete mission enclosure and high church walls. At the center of the town stands the clay and stubble mosque which does not have a minaret and was built in 1995. The ethnographic observation of this architectural endeavour reveals a double split: firstly, between Susana’s transient Muslim population and native Muslims, the latter being the only promoters of the mosque, and within this group, a division between elders who hold the mosque as emblematic of their authority and younger citizens for whom religion provides a new visibility and legitimates their participation in the village’s economic development. The social and religious uses of the mosque (and the church, for that matter), cannot be understood however, without reference to the open spaces of the “religion of the soil”, which provide open cultural spaces in a search for divine law, unlike the enclosed sites of the “revealed word". It is in this palpable triangular relationship, that questions of being, belonging and social organization coexist and evolve daily with relation to the republic of Guinea-Bissau.